Association between preoperative diagnosis of sarcopenia and postoperative pneumonia in resectable esophageal squamous cell carcinoma patients: a retrospective cohort study - Xu, Zhiyun; Wang, Qianwei; Zhang, Zhenzhong; Zhu, Yaning; Chen, Yunyun; Tang, Derong; Zhao, Jianqiang (Frontiers in Oncology, 2023)
Background: Sarcopenia is related to the postoperative outcome of resectable Esophageal Squamous Cell Carcinoma (ESCC) patients. This study evaluated the relationship between sarcopenia and postoperative pneumonia in patients with resectable ESCC. Methods: This was a retrospective analysis of resectable ESCC patients treated from January 2018 to December 2021 with only McKewon procedure. Sarcopenia was evaluated from planning CT scans using skeletal muscles at L3 and defined when PMI < 6.36 cm2/m2 (men) and < 3.92 cm2/m2 (women), respectively. Univariate and multivariate logistic regression analyses evaluating the risk factors for postoperative pneumonia were performed. Results: A total of 773 resectable ESCC patients were included in the study. On the basis of univariate and multivariate analysis, sarcopenia was an independent risk factor for postoperative pneumonia of patients with resectable ESCC (P＜0.05). The stratified analysis showed that gender, age, BMI, smoking or pre-albumin in the logistic regression model did not modify both clinical outcomes (Pinteraction ＞ 0.006). Conclusion: Resectable ESCC patients with sarcopenia had a higher postoperative pneumonia rate after McKewon procedure. To control the incidence of sarcopenia may be important to prevent the occurrence of postoperative pneumonia during perioperative period.